The anti-cyberbullying programs in Finnish lower secondary schools : teacher perspectives - Gazdek, Hrvoje (2021)
The development of technology, methods of communication and the entertainment industry has contributed to an increased amount of time students are spending online. This has also been followed by the emergence of cyberbullying, which has entered schools and has become a serious issue that challenges students, parents and educators alike. Nowadays, schools have to incorporate anti-cyberbullying strategies to ensure a safe learning environment. This study examined the implementation of anti-cyberbullying programs in Finnish lower secondary schools and their potential improvements through the perspectives of educators. Two research questions were in the focus of this study: “How do educators assess the implementation of the current anti-cyberbullying program in their schools” and “How would educators improve the efficiency of the anti-cyberbullying program in their schools?”. The views of the educators were studied through a qualitative approach by using semi-structured interviews. Seven educators from seven different Finnish lower secondary schools shared their experiences with the cyberbullying cases they had encountered. The findings indicated there are several areas within the programs that still have room for improvement, mostly in the area of educating the indirect participants of cyberbullying, i.e., the teachers and parents. Furthermore, the results showed that more attention should be paid to bystanders of bullying. It can be concluded that certain changes need to be made to more efficiently prevent cyberbullying. The facilitation of proper education for teachers, clear school policies about anti-bullying measures and better support for educators to create safer school environments are the first steps to be taken to more efficiently oppose cyberbullying.